Majlis Pra Graduasi dan Apresiasi Pelajar (sesi Mac - Julai 2024) - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
Majlis Pra Graduasi dan Apresiasi Pelajar (Sesi Mac - Julai 2024) was held on 22 November 2024 at Ballroom 2, De Palma Hotel, Shah Alam, to recognise and celebrate outstanding academic achievements among students of Arshad Ayub Graduate Business School (AAGBS) UiTM. A total of 139 students received awards, comprising recipients of Anugerah Pascasiswazah Fakulti (APF), Anugerah Pascasiswazah Cemerlang (ASC), Anugerah Tamat Kedoktoran, and Anugerah Program Mobiliti Pelajar. The ceremony reflected AAGBS's strong commitment to academic excellence, postgraduate development, and international exposure. The event was graced by distinguished guests, including Prof. Dr. Hj. Mohd Sazili Shahibi, Timbalan Naib Canselor (HEP) UiTM; Prof. Dr. Faizah binti Abd Majid, Chief Executive Officer, Institute of Continuing Education & Professional Studies (ICEPS UiTМ); and Dato' Sri Dr. Hj. Irmohizam Ibrahim, Group Managing Director WTCKL and Duta AAGBS. AAGBS UiTM extends its heartfelt congratulations to all award recipients for their exceptional academic achievements and contributions.